A comparative study of the effect of automobile pollution on pulmonary function tests of people who reside in high traffic density urban areas and relatively traffic free rural areas - Amrith Pakkala (CHRISMED Journal of Health and Research, 2014)
Background: Motor vehicle emissions constitute the most significant source of ultra particles in an urban environment. Traffic related air pollution is an occupational health hazard to individuals who live and work in an environment close to traffic. The present study intends to study the effect of air pollution on the pulmonary system in people who reside in areas exposed to automobile exhaust. Material and Methods: This study was conducted by performing pulmonary function tests (PFT) on 20 people who are exposed to automobile exhaust by virtue of their residence nearer to traffic junctions and comparing them with 20 others of age and gender matched and similar anthropometric profile people, who reside in a rural setting free from vehicular air pollution. Statistical analysis was done by Student′s t-test (two-tailed, independent) for inter group analysis. Results: There was a statistically significant difference between the two groups as far as parameters like FVC, FEV 1 , PEFR, FEV 1 /FVC, FEF 25-75% . It can be seen that there is decline in dynamic pulmonary function parameters in the study group when compared to controls, which is statistically significant. Conclusion: The respiratory system are particulate matter (PM 10 ) and sulphur dioxide (SO 2 ) produced by the combustion of fossil fuels. These pollutants react with each other, forming hazardous acid sulfate particles, which are capable of reaching deep inside the tracheo-bronchial tree producing a bronchoconstrictor response, as their predominant site of action are the small airways. This was a comparative study to demonstrate the effect of air pollution due to automobile exhaust on pulmonary functions of people who reside in areas exposed to a polluted urban environment with a similar group in the rural relatively pollution free environment.